Mitochondrial DNA Depletion in Granulosa Cell Derived Nuclear Transfer Tissues - Bebbere, Daniela; Ulbrich, Susanne E.; Giller, Katrin; Zakhartchenko, Valeri; Reichenbach, Horst-Dieter; Reichenbach, Myriam; Verma, Paul J.; Wolf, Eckhard; Ledda, Sergio; Hiendleder, Stefan (Frontiers in Cell and Developmental Biology, 2021)
Somatic cell nuclear transfer (SCNT) is a key technology with broad applications that range from production of cloned farm animals to derivation of patient matched stem cells or production of humanized animal organs for xenotransplantation. However, effects of aberrant epigenetic reprogramming on gene expression compromise cell and organ phenotype, resulting in low success rate of SCNT. Standard SCNT procedures include enucleation of recipient oocytes before the nuclear donor cell is introduced. Enucleation removes the spindle apparatus and chromosomes of the oocyte but also the perinuclear, mitochondria rich, ooplasm. Here we use a Bos taurus model with in vitro fertilized (IVF) and in vivo conceived controls to demonstrate a ~50% reduction of mtDNA in liver and skeletal muscle, but not brain, of SCNT fetuses at Day 80 of gestation. In muscle we also observed significantly reduced transcript abundances of mtDNA encoded subunits of the respiratory chain. Importantly, mtDNA content and mtDNA transcript abundances correlate with hepatomegaly and muscle hypertrophy of SCNT fetuses. Expression of selected nuclear-encoded genes pivotal for mtDNA replication was similar to controls, arguing against an indirect epigenetic nuclear reprogramming effect on mtDNA amount. We conclude that mtDNA depletion is a major signature of perturbations after SCNT. We further propose that mitochondrial perturbation in interaction with incomplete nuclear reprogramming drives abnormal epigenetic features and correlated phenotypes, a concept supported by previously reported effects of mtDNA depletion on the epigenome and the pleiotropic phenotypic effects of mtDNA depletion in humans. This provides a novel perspective on the reprogramming process and opens new avenues to improve SCNT protocols for healthy embryo and tissue development.